The Fibonacci sequence is defined by F 1 = 1 , F 2 = 1 and F n + 2 = F n + 1 + F n for n ≥ 1 . Consider the sequence of every 3rd Fibonacci number, i.e. G n = F 3 n . There are constants a and b such that G n = a G n − 1 + b G n − 2 for every integer n ≥ 2 . What is a + b ?
This problem is posed by Muhammad A.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done!
The recurrence given is equivalent to $$F {3n} = F {3n - 3} + F {3n - 6}$$ so we have $$F 6 = aF 3 + bF 0$$ $$F 9 = aF 6 + bF_3$$ i.e. $$8 = a\cdot 2 + b \cdot 0$$ $$34 = a\cdot 8 + b \cdot 2$$ Solving this system of linear equations yields a = 4 , b = 1 , so $$a + b = \boxed{5}$$
We know that,
a
and
b
are constants, so for any value of
G
N
, the values of
a
and
b
will be same.
Here
G
n
=
F
3
n
,
G
n
−
1
=
F
3
n
−
3
,
G
n
−
2
=
F
3
n
−
6
When,
n
=
3
, then,
F
9
=
a
F
6
+
b
F
3
=
3
4
[ We can easily count
F
9
=
3
4
]
⇒
8
a
+
2
b
=
3
4
....................(1)
When,
n
=
4
, then,
F
1
2
=
a
F
9
+
b
F
6
=
1
4
4
[ We can easily count
F
1
2
=
1
4
4
]
⇒
3
4
a
+
8
b
=
1
4
4
....................(2)
By solving the equation (1) and (2), we shall get
a
=
4
and
b
=
1
So,
a
+
b
=
4
+
1
=
5
[ ANSWER ]
This is not the way to solve it. Suppose it is not given if a and b are constants then how do you know that your scheme works? Mathematics needs general proofs.
A quick solution is to write out part of G ; we get 0 , 2 , 8 , 3 4 , 1 4 4 , ⋯ We know 8 must equal 2 a + 0 b , so a = 4
We now know that 3 4 = 4 × 8 + 2 b = 3 2 + 2 b → b = 1 , thus a + b = 4 + 1 = 5
A more elegant solution uses what we know about F n and G n . We can create an equation G n = F 3 n = F 3 n − 1 + F 3 n − 2 . Thus, G n − 1 = F 3 n − 4 + F 3 n − 5 and G n − 2 = F 3 n − 7 + F 3 n − 8 . Next we can simplify G n recursively into 2 1 F 3 n − 7 + F 3 n − 7 + ⋯ + F 3 n − 7 + 1 3 F 3 n − 8 + F 3 n − 8 + ⋯ + F 3 n − 8 and G n − 1 into 5 F 3 n − 7 + F 3 n − 7 + ⋯ + F 3 n − 7 + 3 F 3 n − 8 + F 3 n − 8 + F 3 n − 8 So we need a and b so that 2 1 = 5 a + b and 1 3 = 3 a + b
Linear combination gives a = 4 , b = 1 → a + b = 4 + 1 = 5
Any thoughts on how to generalize this problem? If G n = F k n for some constant k , are 2 variables sufficient?
Let us take a look at the first 1 2 numbers of the Fibonacci sequence
a n = 1 , 1 , 2 , 3 , 5 , 8 , 1 3 , 2 1 , 3 4 , 5 5 , 8 9 , 1 4 4 …
The third numbers in this segment of the sequence are 2 , 8 , 3 4 , 1 4 4 .
According to the problem, G n = a G n − 1 + b G n − 2 .
Using the "third" numbers we listed above we get the system
{ 8 a + 2 b = 3 4 3 4 a + 8 b = 1 4 4
By solving it, we find that a = 4 and b = 1 , therefore
a + b = 5 .
Since we know the constants exists, we can just write the equation for the particular cases G3 and G2 (we have a system of two liner equations with two unknowns). It easily follows a = 4 and b = 1.
f(3n) =f(3n-1)+f(3n-2) =f(3n-2)+f(3n-3)+f(3n-3)+f(3n-4) =f(3n-3)+2 (f(3n-4)+f(3n-4))+f(3n-5)+f(3n-5)+f(3n-6) reordering them =f(3n-3)+(f(3n-4)+f(3n-5)) 3+f(3n-6) =4*f(3n-3)+f(3n-6)
Great approach! You proved that the formula must hold and provided an explanation for it.
After listing out all Fibonacci numbers up to F 1 5 , we can consequentially determine G 2 , G 3 , G 4 , and G 5 .
G 2 = F 6 = 8 G 3 = F 9 = 3 4 G 4 = F 1 2 = 1 4 4 G 5 = F 1 5 = 6 1 0
Given the definition of G n , we can establish two equations:
G 4 = 1 4 4 = 3 4 a + 8 b G 5 = 6 1 0 = 1 4 4 a + 3 4 b
Solving for a and b , we get 4 and 1, respectively. Thus a + b = 4 + 1 = 5 .
0,1,1,2,3,5,8,13,21,34 34=a(8)+b(2)
G 0 = 0, G 1 = 2, G 2 = 8, G 3 = 34. Then 8 = a * 2 + b* 0, and that impose a = 4. Therefore 34 = 4 * 8 + b * 2. One obtain b = 1. Then a + b = 4 + 1 = 5.
F 3 n + 6 = a F 3 n + 3 + b F 3 n F 3 n + 6 = F 3 n + 5 + F 3 n + 4 = F 3 n + 4 + F 3 n + 3 + F 3 n + 3 + F 3 n + 2 = F 3 n + 3 + F 3 n + 2 + F 3 n + 3 + F 3 n + 3 + F 3 n + 1 + F 3 n = 3 F 3 n + 3 + F 3 n + 2 + F 3 n + 1 + F 3 n = 4 F 3 n + 3 + F 3 n
From the definition of the Fibbonacci sequence:
F 3 n = a F 3 ( n − 1 ) + b F 3 ( n − 2 ) for all n ≥ 2
Let n = 2 :
F 6 = a F 3 + b F 0
F 6 = 8 , F 3 = 2 , F 0 = 0
8 = 2 a + 0 b
a = 4
Let n = 3 :
F 9 = 4 F 6 + b F 3
F 9 = 3 4 , F 6 = 8 , F 3 = 2
3 4 = 4 ∗ 8 + 2 b
2 b = 2
b = 1
a + b = 4 + 1 = 5
G0 = F0 = 0,
G1 = F3 = 1,
G2 = F6 = 5,
G3 = F9 = 21
and so on...
so we get G sequence as
0, 1, 5, 21, 89...
now for n >= 2, from the given equation,
G2 = aG1 + bG0 = 5 ,
G3 = aG2 + bG1 = 21 ,
G4 = aG3 + bG2 = 89 ,
we can see a pattern here
like 5 = 4(1) + 1 ,
21 = 4(5) + 1(1) ,
89 = 4(21) + 1(5) ,
comparing this with the previous equations, we get a=4 and b=1
F(3n)=F(3n-1)+F(3n-2)
G(n)=F(3n-2)+F(3n-3)+F(3n-3)+F(3n-4)
G(n)=F(3n-3)+F(3n-4)+2xF(3n-3)+F(3n-4)
G(n)=3xF(3n-3)+2xF(3n-4)
G(n)=3xG(n-1)+2x[F(3n-5)+F(3n-6)]
G(n)=3xG(n-1)+F(3n-4)+F(3n-5)+F(3n-5)+F(3n-6)+F(3n-6)-F(3n-4)
G(n)=3xG(n-1)+F(3n-3)+F(3n-6)
G(n)=4xG(n-1)+G(n-2)
Hence a+b is 5
First, we have G(0) = 0; G(1) = 2; G(2) = 8; G(3) = 34; G(4) = 144 .... Then, we can predict that G(n+2) = G(n+1) + 4.G(n) I think it's easy to prove this equation by inductive method.
Since we know that Gn = a(Gn-1) + b(Gn-2) we can express this as a sistem of two linear equations. They will be: 34(which is the 9th number of the Fibonacci sequence) = 8a(8 is equal than the 6th number of the Fibonacci sequence) + 2b(2 is equal than the 3th number of the Fibonacci sequence). We can do the same for higher numbers in Fibonacci sequence and we will get that: 144(12th number) = 34a(9th number) + 8b(6th number). Solving this linear equations we get: a = 4 and b = 1. And so, a + b = 5 SOLVED
G1=f3=2, G2=f6=8, G3=f9=34=8a+2b, G4=f12=144=34a+8b. From the first and second equation we get a=4 and b=1. So, a+b=5
G0=0, G1=2, G2=8, G3=34. G2=aG0+bG1, 8=2b. G3=aG1+bG2, 34=2a+8b. Solving the simultaneous equations, a=1, b=4, a+b=5.
Problem Loading...
Note Loading...
Set Loading...
For any n we can use the recurrence relation for F to find:
F n + 2 = F n + F n + 1
F n + 3 = F n + 2 F n + 1
F n + 4 = 2 F n + 3 F n + 1
F n + 5 = 3 F n + 5 F n + 1
F n + 6 = 5 F n + 8 F n + 1
Inspecting this list, we see that F n + 6 = 4 F n + 3 + F n
so the required coefficients are 4 and 1 .